2016
DOI: 10.22146/jieb.10320
|View full text |Cite
|
Sign up to set email alerts
|

Role Conflict and Role Ambiguity on Local Government Internal Auditors: The Determinant and Impacts

Abstract: The bureaucratic reform at the local government level in Indonesia that was instituted in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
6
0
2
Order By: Relevance
“…It means that the lower the value of role conflict will encourage increased auditor independence, so that it will improve the quality of internal audit. The results are in line with previous studies highlighting the mediating effect of auditor independence in the relationship between role conflict on internal audit quality [31,32].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It means that the lower the value of role conflict will encourage increased auditor independence, so that it will improve the quality of internal audit. The results are in line with previous studies highlighting the mediating effect of auditor independence in the relationship between role conflict on internal audit quality [31,32].…”
Section: Resultssupporting
confidence: 92%
“…Aghghaleh et al [28], Alleyne et al [29], and Mukhtaruddin [30] revealed that auditor independence is likely able to strengthen the effect of role ambiguity on the quality of internal audit. Moreover, previous studies [31,32] have found the mediating effect of auditor independence in the relationship between role conflicts on internal audit quality.…”
Section: H9: Audit Planning Has a Positive Effect On Internal Audit Qualitymentioning
confidence: 88%
“…The relationships between role conflict and role ambiguity and managerial practices, leader behavior, job satisfaction, anxiety, and turnover intention provide evidence of the tool’s validity [ 8 ]. More recent studies have reported similarly satisfactory estimates of internal consistency for the ROQ, for example, Orgambídez and Almeida: ω = 0.92 and 0.85 for RA and RC, respectively [ 30 ], and Novriansa and Riyanto: composite reliability = 0.80 and 0.79 for RA and RC, respectively [ 31 ]. A 21-nation study of role conflict and role ambiguity reported alpha coefficients of 0.54 and 0.87, respectively, for the use of the ROQ scale with South African participants [ 32 ].…”
Section: Methodsmentioning
confidence: 91%
“…Individu yang mengalami stres berisiko mengalami kelelahan emosional, depersonalisasi, ketidakpuasan, komitmen kerja menurun, sehingga memicu tindakan kontra-produktif (Ortqvist & Wincent, 2006;Spector & Fox, 2005). Beberapa artikel ilmiah di Indonesia telah membahas tentang stres peran (Abduh dkk., 2019;Hambali dkk., 2016;Lase dkk., 2019;Novriansa & Riyanto, 2016;Partina, 2013;Prasetyo, 2011;Pratiwi dkk., 2019). Akan tetapi, peneliti belum pernah menemukan artikel ilmiah yang khusus membahas proses adaptasi Skala Stres Peran (Role Stressor Scale) ke dalam bahasa dan budaya Indonesia.…”
Section: Pendahuluanunclassified